2020
DOI: 10.24106/kefdergi.683577
|View full text |Cite
|
Sign up to set email alerts
|

An Examinatıon Of The Computational Thinking Skills: Sample Of Vocational High Schools

Abstract: Bu araştırmada lise öğrencilerinin Bilgi-işlemsel Düşünme (BİD) becerileri incelenmiş ve BİD becerileri bazı değişkenler açısından karşılaştırılmıştır. Araştırmanın örneklemini meslek lisesinde öğrenim gören 591 öğrenci oluşturmaktadır. Öğrenciler %51.1'i yüksek, 44.3'ü orta ve %4.6'sı düşük düzeyde BİD becerisine sahiptirler. Araştırma sonuçları BİD becerilerinin cinsiyet, programlama dersi alma, programlama deneyimi ve bilgisayar sahipliği açısından farklılaşmadığını göstermiştir. Okul türü ve sınıf düzeyi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Results showed that there was no significant difference in CT skills of the students according to gender. This finding is parallel to many studies (Alsancak Sarıkaya, 2019;Atmatzidou & Demetriadis, 2016;İbili et al, 2020;Korucu et al, 2017;Mindetbay et al, 2019;Oluk & Korkmaz, 2016;Tsai et al, 2021;Wu & Su, 2021;Yağcı, 2018). In the light of these findings, it can be said that gender does not play an active role in CT.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Results showed that there was no significant difference in CT skills of the students according to gender. This finding is parallel to many studies (Alsancak Sarıkaya, 2019;Atmatzidou & Demetriadis, 2016;İbili et al, 2020;Korucu et al, 2017;Mindetbay et al, 2019;Oluk & Korkmaz, 2016;Tsai et al, 2021;Wu & Su, 2021;Yağcı, 2018). In the light of these findings, it can be said that gender does not play an active role in CT.…”
Section: Discussionsupporting
confidence: 85%
“…In the study conducted by Alsancak Sarıkaya (2019), it was concluded that there was no significant difference in CT skills between students who saw themselves as novice and intermediate level programming skills. In another study, Ibili et al (2020) reported that CT skills did not differ based on students' programming experience. That may be due to the difference in educational approaches, techniques, and activities in the teaching programming environment (Erümit et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…In the literature, concepts related to computational thinking skills are discussed as abstraction, generalization, algorithmic thinking, collaborative and critical thinking, creativity, problem-solving, and communication skills (İbili, Günbatar, & Sırakaya, 2020;Sırakaya, 2019;Uslu, Mumcu, Egin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Computational skill is also a popular subject among researchers. While many studies have been found on CT in the literature, these studies mostly concentrate on the definition and scope of this skill in addition to CT levels of learners and educators in different branches (Akman & Bircan, 2021;Aydoğdu, 2020;Critten et al, 2022;Çakır & Yaman, 2018;Çakır et al, 2019;Çelik Arslan, 2021;Çiftci et al, 2018;Çimentepe, 2019;Dagienė et al, 2022;Dolmacı & Akhan, 2020;Fessakis & Prantsoudi, 2019;Gabriele et al, 2019;İbili, Günbatar, & Sırakaya, 2020;Kirmit et al, 2018;Korkmaz et al, 2015;Kousis, 2019;Oluk & Korkmaz, 2016;Oluk & Çakır, 2019;Özçınar & Öztürk, 2018;Özkan-Hıdıroğlu & Hıdıroğlu, 2021;Özkeş, 2016;Rehmat et al, 2020;Sade, 2020;Sayın, 2020;Ünsal Serim, 2019;Yang et al, 2020;Yünkül, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%